CCR7 in Blood Cancers – Review of Its Pathophysiological Roles and the Potential as a Therapeutic Target - Cuesta-Mateos, Carlos; Terrón, Fernando; Herling, Marco (Frontiers in Oncology, 2021)
According to the classical paradigm, CCR7 is a homing chemokine receptor that grants normal lymphocytes access to secondary lymphoid tissues such as lymph nodes or spleen. As such, in most lymphoproliferative disorders, CCR7 expression correlates with nodal or spleen involvement. Nonetheless, recent evidence suggests that CCR7 is more than a facilitator of lymphatic spread of tumor cells. Here, we review published data to catalogue CCR7 expression across blood cancers and appraise which classical and novel roles are attributed to this receptor in the pathogenesis of specific hematologic neoplasms. We outline why novel therapeutic strategies targeting CCR7 might provide clinical benefits to patients with CCR7-positive hematopoietic tumors.